A new Cd(ii)-based metal–organic framework for highly sensitive fluorescence sensing of nitrobenzene. Issue 12 (27th February 2015) - Xia, Yu-Pei; Li, Yun-Wu; Li, Da-Cheng; Yao, Qing-Xia; Du, Yu-Chang; Dou, Jian-Min
Abstract : A Cd(ii )-based MOF was synthesized from a new flexible multidentate ligand H4 L . The MOF reveals different fluorescence responses to various organic analytes. This phenomenon indicates that this MOF may be a good probe for detecting nitrobenzene. Abstract : A Cd(ii )-based metal–organic framework, {[Cd2 L(H2 O)2 ]·DMF·H2 O} n (1 ), has been successfully constructed from a new flexible antler-like multidentate ditopic ligand (H4 L ). This metal–organic framework shows highly sensitive fluorescence sensing of nitrobenzene.